Understanding environmental policy convergence : the power of words, rules and money - Jorgens, Helge, 1967-; Lenschow, Andrea; Liefferink, Duncan (New York : Cambridge University Press, 2014)
'Over recent decades national environmental policies have become increasingly alike. This book analyses the driving forces of this process of policy convergence, providing an in-depth empirical analysis of the international forces at work. It does so by investigating how four countries - France, Hungary, Mexico and the Netherlands - have shaped their domestic environmental policies in the context of international institutions and relationships, while taking into account various domestic factors and national conditions. Employing a qualitative approach, the authors seek to deepen understanding of the processes and mechanisms through which international forces such as legal harmonisation, institutionalised information flows and global trade dynamics affect domestic environmental policy change. Together with its companion volume Environmental Policy Convergence in Europe: The Impact of Trade and International Institutions (2008) this book provides a'showcase' of mixed methodologies, combining quantitative and qualitative approaches in an innovative way'--
1. Introduction: theoretical framework and research design / Duncan Liefferink, Helge J$1'Xr(Bgens and Andrea Lenschow --s 2. Is there convergence of national environmental policies? An analysis of policy outputs in 24 OECD countries / Katharina Holzinger, Christoph Knill and Thomas Sommerer -- 3. Regulation of industrial discharges into surface water / Stephan Heichel, Jessica Pape and Jale Tosun -- 4. Taming the'tiger in the tank': explaining the convergence of limit values for lead in petrol / Per-Olof Busch -- 5. Cross-national convergence of traffic noise policies / Dieter Pesendorfer -- 6. National policies for cleaning up contaminated sites / Sietske Veenman -- 7. Converging ideas about risk regulation? The precautionary principle in national legal systems / Dieter Pesendorfer -- 8. From the outside in: explaining convergence in the legal recognition of the sustainability principle / Per-Olof Busch and Helge J$1'Xr(Bgens --s 9. Complex causation in cross-national environmental policy convergence / Andrea Lenschow, Duncan Liefferink and Helge J$1'Xr(Bgens.s
Includes bibliographical references and index.
Keywords: Environmental policy -- International cooperation -- Case studies; Environmental management -- International cooperation -- Case studies; Global environmental change -- International cooperation -- Case studies; POLITICAL SCIENCE / General; Environmental management -- International cooperation; Environmental policy -- International cooperation; Global environmental change -- International cooperation; Case studies